Towards efficient photoanodes for solar fuel production - Shaheen, Basamat Saif El Din (AUC Knowledge Fountain, 2014)
The solar energy conversion efficiency is a materials-limited process as there is always a trade-off between the light absorption capability of the material and its stability. For solar hydrogen production, for example, wide-bandgap semiconductors are stable but only absorb in the UV region of the light spectrum. Small-bandgap semiconductors, on the other hand, are not stable in aqueous electrolytes. In this thesis, two metal oxide-based photoanode systems were studied in an attempt to find a balance between their optical and photocatalytic properties as well as their stability. In the first part of the thesis, one-dimensional TiO2 nanotubes/ZnO core-shell nanostructured electrodes were investigated. Increasing the ZnO shell thickness resulted in different morphological, structural and optical characteristics. The crystallinity of the core nanotubes was found to be a determinant factor in the formation of the TiO2/ZnO heterojunctions as revealed by the FESEM, GAXRD, XPS and Raman analyses. The TiO2/ZnO heterojunction showed almost 80% increase in the photoconversion efficiency (7.3%) compared to pure TiO2 (4.1%) under UV illumination (320-400 nm, 100 mW/ cm2, 0.5 M Na2SO4). The main reasons responsible for the observed enhancement in the photoactivity were discussed. In the second part of the thesis, Nb2O5 based photoanodes were investigated. The fabrication of Nb2O5 ordered structures (nanopores, nanorods, nanochannels and microcones) is achieved by a simple electrochemical method. The microcone structure was the most stable morphology and showed higher absorption ( 450 nm) compared to other structures (380 nm). An in-situ approach for the direct synthesis of crystalline Nb2O5 microcones at room temperature is demonstrated for the first time. Also, the successful formation of niobium oxynitride microcones is achieved for the first time as confirmed via XPS, XRD and Raman spectroscopy measurements. The fabricated NbON microcones showed exceptional optical properties with an absorption profile extending to 770 nm.